Molecular Therapeutic Potency of Metformin by Targeting p53-Related Molecules in Mutant p53 Colon Cancer Cell Line - Dyah R. Budiani; Melani R. Mahanani; Yohanes C. Wibowo; Ari Probandari; Diding H. Prasetyo; Ambar Mudigdo (Indonesian Journal of Cancer Chemoprevention, 2016)
Colon cancer is a malignancy in gastrointestinal tract. It causes high mortality rate in global cancer population. However, chemotherapy as its first option therapy is still controversial due to its effectiveness and its adverse effects. Finding supportive and alternative drugs to cure cancer is one of focus in cancer research. A drug which also has anticancer effects is metformin. Metformin is a biguanide antidiabetic which show its potential anticancer benefit in metabolic-related cancers including colon cancer. To investigate anticancer potency of metformin in targeting p53-related molecules. Metformin treatment were divided into 4 groups by 0, 5, 10 and 20 mM concentrations and incubated in 37o C and 5 % CO2 condition for 48 hours. Immunohistochemistry were conducted to asses level of expression of Bax, p21, cyclin D1 and E2F1, respectively. Level of expression were measured by H-SCORE using percentage and intensity calculation. Comparisons of H-SCORE between groups were performed by ANOVA for parametrical data and Kruskal-Wallis for non-parametrical data. Growth inhibition were observed after metformin treatment. Metformin increases Bax expression significantly at all concentrations. p21 expression was also increased after metformin treatment but is not statistically significant. Subsequently, metformin decreases cyclin D1 expression at 10 and 20 mM concentration thus decreased E2F1 expression at 5 and 10 mM concentration. These data suggest that metformin may have potential therapeutic effects in mutant p53 colon cancer cell line by targeting p53-related molecules.Keywords: Colon cancer; p53; Biguanide; Metformin; p53-mutant cell line